Case Report: SPECT-CT-guided minimally invasive transverse process resection for Bertolotti syndrome - Spellicy, Samantha E.; O'Callaghan, Ellen; Patetta, Michael; Turner, Dennis A.; Abd-El-Barr, Muhammad M. (Frontiers in Surgery, 2026)
Lumbosacral transitional vertebrae (LSTV) are a common congenital anomaly that often manifests as chronic low back or radicular pain, a condition clinically referred to as Bertolotti syndrome. One specific cause of Bertolotti syndrome is pseudoarticulation of the L5 transverse process with the sacrum or ilium due to LSTV. Although conventional magnetic resonance imaging (MRI) and computed tomography can identify structural changes, they provide limited functional information regarding sites of active arthropathy. Single-photon emission computed tomography (SPECT-CT) enables the localization of metabolically active pseudoarthrotic joints, thereby improving patient selection and surgical planning. We present the case of a 52-year-old woman with Bertolotti syndrome who presented with severe chronic axial back pain and left-sided pain radiating along portions of the L5 and S1 dermatomes. MRI revealed no significant compression of the neural elements but did demonstrate an incidental Tarlov cyst at S1, measuring 5.7 mm × 5.7 mm. SPECT-CT demonstrated localized, abnormal uptake between an anomalous left L5 transverse process and the sacrum. The patient underwent minimally invasive, image-guided removal of the left L5 transverse process, isolating L5 vertebral motion from the iliac crest. She was discharged on postoperative day 1 with significant improvement in her pain and radiculopathy. At 6-week, 3-, and 6-month follow-up, she reported near-complete resolution of presurgical radicular pain, functional restoration, and a return to normal activities. This case highlights the utility of SPECT-CT in evaluating Bertolotti syndrome. Functional imaging enabled precise structural localization of the pain generator, while targeted minimally invasive resection provided durable symptom relief.